Efektivitas pemberdayaan peternak broiler melalui pola kemitraan inti plasma oleh PT. Jaguar Farm di Kabupaten Malang - Prabowo, Jendro Adi; Irdaf, Irdaf; Azizah, Siti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
This qualitative research was conducted in PT. Jaguar Farm from 18 May to 28 June 2016. Sample was purposively selected using snowball sampling method followed by in-depth interviews. Data was analysed using descriptive analysis. The results showed that Standard Operating Company of  PT. Jaguar Farm was not too difficult and can be understood by all farmers. But the system seemed to be still one-sided contract which was determined only by the company, while farmers did not have a bargaining position to adjust the contract awarded. The patron-client system run by PT. Jaguar Farm was relatively new so that the clients who joined the company’s business were mostly small farmers, in the sense that they still required assistance in the form of capital, extension and marketing. Another finding showed however that the client had a problem in the delay time of harvesting process. Therefore, the study concluded that PT. Jaguar Farm as the core in the patron-client business was able to show good enough performance, but there were some drawbacks that possibly could harm farmers. Keywords: Partnership, contract farming, breeding farm, empowerment